Kyai Syam’un’s Prophetic-Nationalistic Leadership in Islamic Educational Development in Banten, Indonesia: A Historical Study - Bachtiar, Machdum; Anshori, Irfan; Zaitun, Zaitun; Wasehudin, Wasehudin; Lazzavietamsi, Fandy Adpen (POTENSIA: Jurnal Kependidikan Islam, 2026)
This study examines the prophetic–nationalistic leadership of Kyai Syam’un in the development of Islamic education in Banten. Prophetic–nationalistic leadership is defined as a leadership model that integrates prophetic values—sidq, amanah, tabligh, and fatanah—with the spirit of nationalism, patriotism, and social responsibility in educational practice. The main focus of this study is Kyai Syam’un’s contribution to the development of Islamic education in Banten, including the establishment of Islamic educational institutions, cadre formation, da’wah activities, character building, and strengthening of national values. This study employs a historical method consisting of heuristics, source criticism, interpretation, and historiography. The data were obtained from historical documents, archival records, field observations of historical sites such as the Al-Khairiyah Islamic educational institution, as well as interviews with informants who have historical connections with Kyai Syam’un, including Mufti Ali and Ali Mujahidin. Historical struggle is positioned as a contextual background that shaped the character of leadership, rather than the main focus of the study. The findings show that Kyai Syam’un’s leadership made a significant contribution to the development of Islamic education in Banten through the integration of Islamic values, discipline, patriotism, cadre formation, and social commitment within educational institutions such as Al-Khairiyah. His leadership model reflects a synthesis of religious values and national consciousness in educational practice. This study contributes to the field of Islamic educational leadership by offering a prophetic–nationalistic leadership model based on Islamic ethical values and national commitment, providing a conceptual framework for understanding the role of Kyai in developing character-based and nation-oriented Islamic education.